Analysis of financial management decisions on company financial performance with economic value added (eva) as a mediating variable - Ainun Jariah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In a competitive business environment, financial management decisions such as funding decisions, investment decisions, and dividend policies are key elements that influence a company's operational efficiency and financial performance. However, the direct impact of these decisions is often complex, involving mediating variables such as Economic Value Added (EVA). EVA measures the economic value added generated by a company after accounting for the cost of capital, where a positive EVA value indicates strong performance. Despite its importance, research explicitly exploring the relationship between EVA, financial management decisions, and financial performance is limited. This study aims to evaluate the simultaneous and partial effects of financial management decisions on financial performance and EVA, as well as the mediating role of EVA. This study uses an exploratory and survey-based approach with secondary data taken from the financial statements of 150 manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2017. A total of 37 companies were selected by purposive sampling and analyzed using SPSS and path analysis. The results showed that EVA is not significantly influenced by financial management decisions, either partially or simultaneously. Financial performance is partially influenced by funding and investment decisions but not significantly by EVA. In addition, EVA does not mediate the relationship between financial management decisions and financial performance. These findings indicate that although EVA provides insight into value creation, its role as a mediator in financial decision making is limited. The implications of this study are important for the development of theory and practice of corporate financial management.